2004
DOI: 10.1037/0021-843x.113.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Post-Event Rumination and Negative Self-Appraisal in Social Phobia Before and After Treatment.

Abstract: This study investigated the relationship between self-appraisals of performance, symptom severity and post-event rumination in social phobia, and evaluated the effect of treatment on these variables. A socially phobic group and a nonanxious control group performed an impromptu speech and were told that their performance would be evaluated. Participants appraised their performance immediately after the speech and 1 week later, and the frequency of post-event rumination during the week following the speech was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
217
2
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(249 citation statements)
references
References 32 publications
(52 reference statements)
19
217
2
7
Order By: Relevance
“…A significant difference between predicted and actual estimates is considered to derive from the individual's feelings of 'transparency' and/or being in the 'social spotlight' and his or her inability to form an accurate self-representation. Indeed, the way in which the spotlight effect and the illusion of transparency are measured is similar to studies showing a discrepancy between socially anxious individuals' self-ratings of performance and ratings provided by others (Abbot & Rapee, 2004;Alden & Wallace, 1995;Mansell & Clark, 1999;McEwan & Devins, 1983;Mellings & Alden, 2000;Rapee & Lim, 1992;Stopa & Clark, 1993).…”
mentioning
confidence: 57%
“…A significant difference between predicted and actual estimates is considered to derive from the individual's feelings of 'transparency' and/or being in the 'social spotlight' and his or her inability to form an accurate self-representation. Indeed, the way in which the spotlight effect and the illusion of transparency are measured is similar to studies showing a discrepancy between socially anxious individuals' self-ratings of performance and ratings provided by others (Abbot & Rapee, 2004;Alden & Wallace, 1995;Mansell & Clark, 1999;McEwan & Devins, 1983;Mellings & Alden, 2000;Rapee & Lim, 1992;Stopa & Clark, 1993).…”
mentioning
confidence: 57%
“…Specific events appear to trigger these sets of affective, cognitive, and behavioral responses that remain embedded in the social context, in contrast to those experienced with the continuity associated with traits. While some studies have evidenced continuity (Abbott & Rapee, 2004;Lundh & Sperling, 2002), in the current study across time stabilities were evident in some individuals more than others, suggesting that the degree to which the set of reactions associated with social anxiety are embedded as stable proclivities may vary across individuals at this particular period of developmental transition when adolescents leave home to attend college for the first time. Recognizing the power of the situation, and processes operating within the situation, is vital in identifying specific elements that can potentially be modified in an attempt to interrupt the maladaptive processes and establish more adaptive ones.…”
Section: Individual Variability In the Dynamics Of Social Anxietymentioning
confidence: 83%
“…Research has also pointed to post-event rumination as an important variable in the maintenance of social anxiety (Abbott & Rapee, 2004;Dannahy & Stopa, 2007;Mellings & Alden, 2000). During post-event rumination, individuals high in social anxiety revisit their social experience, focusing on memories of the anxiety they experienced and their perceived negative self-performance, in part because these aspects of the experience received greater encoding and stronger storage in memory due to their high attentional salience in vulnerable individuals (Kocovski, Endler, Rector, & Flett, 2005).…”
mentioning
confidence: 99%
“…[12] For example, it has been shown that individuals with SAD had a more negative appraisal of an impromptu speech task 1 week after the task, whereas nonanxious individuals developed a more positive attitude about their performance. [13] Moreover, successful psychological treatment improved perceptions of performance and reduced negative rumination.…”
Section: Targeting Of Safety Behaviorsmentioning
confidence: 99%